Mapping The Walkability Of Main Campus, Universiti Sains Malaysia Using Geographic Information System (Gis) - Habib, Mohammad Faizul Aman Mohammed (Universiti Sains Malaysia, 2022)
In the USM community, walkability has grown to be essential for integrating sustainability at all levels. Students' growing willingness to drive motorized vehicles on campus, in particular, has become a source for concern because doing so, contributes to campus pollution. This problem goes against the Sustainable Development Goals (SDG) Agenda, which aims to achieve social harmony, economic prosperity, and environmental protection. In order to address this problem, the initial goal of this study is to evaluate every accessible route segment in the USM Main Campus to determine how well it performs in terms of walkability for the entire area of the campus, which has been separated into 8 zones. Indicators including connectivity, sidewalk slope, wheelchair accessibility, surface degradation, street furniture, shades, shelters, obstructions, green spaces, and the existence of left and right positions for pedestrian pathways are considered while evaluating each segment of the route. The next stage was to determine each zone's walkability performance based on the evaluation results. The capability of QGIS software to differentiate the performance of each zone allows for the visualisation of data regarding each zone's walkability by producing a map. The QGIS map's results provide crucial information about which zones have the highest and lowest walkability performance, making it easier to decide what measures should be taken to improve walkability both in that zone and throughout the campus area as a whole. According to this study, Zone 1 had the highest walkability performance with a score of 61%, while Zone 2 had the lowest walkability performance with a score of 43%. Therefore, steps must be taken to enhance walkability among campus residents and maximise the chance that these incredibly difficult transformations toward a more accessible, sustainable, and healthy campus will succeed.